Selisik Tindak Pidana Kenakalan ‘Perundungan Fisik’ Anak Di Lingkungan Sekolah Berdasarkan Aspek Hukum Pidana - Rahma, Meida Adita; Fitriasih, Surastini (Universitas Semarang, 2024)
The purpose of this study is to analyze criminal acts related to the phenomenon of bullying among children in school environments, focusing on the delinquency of children aged 12-18 years in the form of physical violence such as bullying. This research particularly emphasizes the role of educators in handling bullying, which impacts the understanding of both the physical and psychological effects of bullying. This study uses a normative research method. Bullying that is considered a 'joke' can have a domino effect and have fatal consequences. Education by educators and parents, counseling or socialization, and the role of the community are very important to prevent and overcome bullying. The research findings reveal that bullying constitutes a criminal offense categorized within the realm of violence against children, with various underlying factors contributing to its occurrence. It is noteworthy that approximately 341 victims of physical bullying, involving severe assault resulting in serious injuries or fatalities, have been documented. Tujuan penelitian ini adalah untuk menganalisisTindak Pidana yang berkaitan dengan fenomena perudungan anak di lingkungan sekolah, dengan fokus pada kenakalan anak usia 12-18 tahun dalam bentuk kekerasan fisik seperti perundungan. khususnya peran tenaga pendidik dalam menangani tindakan perudungan yang berdampak pada pemahaman dampak dari perudungan fisik maupun psikologisPenelitian ini menggunakan metode penelitian normatif. Perundungan yang dianggap sebagai ‘gurauan’ dapat memberikan domino effect dan berakibat fatal. Edukasi oleh tenaga pendidik dan orang tua, adanya konseling ataupun sosialiasi, peran dari masyarakat sangat penting untuk mencegah dan menanggulangi perundungan. Hasil penelitian menunjukkan Kejahatan perundungan merupakan suatu tindak pidana yang tergolong ranah kekerasan terhadap anak dengan dilatarbelakangi berbagai macam faktor penyebab. Tercatat kurang lebih 341 korban perundungan anak golongan kekerasan fisik berupa penganiayaan menimbulkan luka berat hingga meninggal dunia.